Cytogenetic and molecular diagnostic testing associated with prenatal and postnatal birth defects. Issue 4 (1st March 2020) - Berisha, Stela Z.; Shetty, Shashi; Prior, Thomas W.; Mitchell, Anna L.
ABSTRACT: Genetic testing is beneficial for patients and providers when in search of answers to medical problems related to the prenatal or early postnatal period. It can help to identify the cause or confirm a diagnosis associated with developmental delay, intellectual disability, dysmorphic features, heart defects, multiple malformations, short stature, stillbirth, neonatal death, or fertility problems. Genetic testing can be used to rule out single‐gene or chromosome abnormalities. Different diagnostic cytogenetic and molecular genetic techniques are applied in clinical genetics laboratories, from conventional ones to the state of the art chromosomal microarrays and next‐generation sequencing. Each of the genetic techniques or methods has its strengths and limitations, however different methods complement each‐other in trying to identify the genetic variation(s) responsible for a medical condition, especially the ones related to birth defects.